Epidemiological analysis of tuberculosis in São Luís - MA - Aragão, Francisca Bruna Arruda; Arcêncio, Ricardo Alexandre; Carneiro, Tânia Gomes; De Assis Cândido, Fernanda Carla; Da Silva Cunha, José Henrique; Reis, Andréa Dias [UNESP]; Fiorati, Regina Célia (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2020)
Objective: Analyzing the occurrence of Tuberculosis registered in São Luís. Method: This is a descriptive epidemiological study, with data obtained from the Notifiable Diseases Information System (SINAN/Tuberculosis) from 2014 to 2016. Descriptive statistics with the calculation of absolute and relative frequency was applied for categorical variables and position and dispersion measures for metric variables. Results: 2,306 cases were found in 378 residential neighborhoods. In 2014, the most affected District was the Vila Cidade Olímpica with 50 cases; in 2015, it had 39 cases, and in 2016 it had 25 cases. Conclusion: The study broadens the knowledge since it presents the epidemiological profile of Tuberculosis cases in São Luís. It was observed that the majority of cases were male, with economically active age, brown ethnic group, and complete secondary education.
Análise epidemiológica da tuberculose em São Luís - MA
Keywords: Epidemiology; Health Evaluation; Prevalence; Social Determinants; Tuberculosis